ANALISIS PENGUNAAN KATA KONKRET DALAM KUMPULAN PUISI TIRANI DAN BENTENG KARYA TAUFIK ISMAIL SEBAGAI ALTERNATIF BAHAN AJAR BAHASA INDONESIA PADA FASE D - Hasrul, Hasrul; Titin Nurhayatin (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
This study was motivated by the low ability of students to analyse linguistic rules in poetry and the limited teaching materials available on identifying linguistic rules in poetry. The problem addressed in this study focuses on the use of concrete words in poetry. This study was conducted with the aim of examining concrete words related to the senses of sight, hearing, smell, touch or movement, and temperature or taste; which concrete words are used most frequently; and the results of this study on concrete words are used as teaching materials for Indonesian language for students in phase D. The object of this study is the collection of poems Tirani dan Benteng by Taufik Ismail, with a sample of 17 poems. The research approach used is a qualitative descriptive approach, which aims to describe the results of the analysis of the use of concrete words in the collection of poems Tirani dan Benteng by Taufik Ismail. Data collection was conducted through data analysis, grouping data according to the aspects being studied, creating data tables, and analysing them using an appropriate theoretical framework, followed by detailed interpretation and drawing conclusions based on the research stages that had been completed. The findings of this study indicate that the concrete words used in the poetry collection Tirani dan Benteng, from 17 poetry samples analysed, include concrete words related to sight, hearing, touch or movement, and temperature or taste. The highest frequency of concrete word usage was visual concrete words, with 89 out of a total of 149 concrete words. The 17 poems contained strong concrete words and were presented in a communicative and easy-to-understand style. The results of this study can be used as teaching materials for Indonesian language for students in phase D. Keywords: concrete words, poetry, teaching materials, Indonesian language.